Перетворення просторових координат у координати простору камери при адаптивному візуальному управлінні - Павленко, Т. І. (ХНУРЕ, 2019)
The given work is devoted to the modern developments in the field of robotics using adaptive visual control. Investigation is carried out in the target space, the desired trajectory of WMR (wheel mobile robot) generated by specifying a robot that moves in camera space by the following dynamic trajectory. The main purpose of the control is to convert the WMR parameters to track the trajectory generated in the space of the chamber due to parametric uncertainty.
Keywords: desized trajectory; wheel mobile robots; parametric uncertainty